Reducing air pollution and occupational health risk using palm olein abrasive blasting for metal surface cleaning applications - Zakaria, Hanis; Hassan, Suhaimi; Azmi, Mohd Azham (Penerbit UTHM, 2020)
Abrasive blasting process done for surface cleaning which has two methods which are dry or wet process. The dry process which uses abrasive media blasted onto a surface to clean the surface normally will release fine dust into the environment. Water used with abrasive media to reduce the dust release into the environment; named as wet abrasive blasting. However, water causes corrosion to metal surface. In this study, analysis of refined, bleached and de-odorized (RBD) palm olein as an alternative to the use of water in wet abrasive blasting process will be investigated. The analysis in this study covers personal dust exposure reduction, emission rate reduction and corrosion inhibition. In this research, abrasive blasting workers’ exposure level to the dust release from abrasive blasting activity will be determined using NIOSH Method. EPA-42 will be used to determine the emission rate. XRD, ICP-MS and SEM also will be used to determine the dust and material composition. To see the effectiveness of the RBD palm olein as a corrosion inhibitor, samples of metal surface will be tested using ASTM method. For the expected results, the quality of RBD palm olein expected to show similar result to dry and wet abrasive blasting in cleaning performance. Exposure monitoring result expected to show that the workers’ exposure to dust release from RBD palm olein abrasive blasting reduced the respirable and inhalable dust compared to the result recorded in dry abrasive blasting.